National systems of law and european integration (Contemporary Central & East European Law, 2002)
Poland’s integration with the European Communities is, as it follow from our reflections, a fdifficult proces, which requires deep systemic changes that must occur within the framework of the transformation of the State system, which has been going on for ten years already and has been completed yet. Without continuing the transformation Paland has no chance for a real integration.